2020
DOI: 10.2169/internalmedicine.3473-19
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ipragliflozin on the Renal Function and Serum Uric Acid Levels in Japanese Patients with Type 2 Diabetes: A Randomized, 12-week, Open-label, Active-controlled Trial

Abstract: Objective To examine the add-on effects, compared to the existing antidiabetes treatment, of the sodiumglucose cotransporter 2 inhibitor ipragliflozin on glycemic control and the risk factors of cardiovascular disease (CVD) and chronic kidney disease (CKD) in patients with inadequately controlled type 2 diabetes. Methods This 12-week, randomized, open-label, active-controlled trial included 30 patients with type 2 diabetes who were randomized 1:1 to ipragliflozin and control groups (n=15 each). The ipraglifloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…After further screening, 19 RCTs with 39 arms fulfilled the inclusion criteria and were eventually included in the present study (Figure 1). These RCTs incorporated 4218 adult participants with T2DM, and six SGLT-2 inhibitors were included: empagliflozin, [25][26][27][28] dapagliflozin, [29][30][31][32][33] canagliflozin, 34 ipragliflozin, [35][36][37][38] luseogliflozin [39][40][41] and tofogliflozin. 42,43 In addition, the following baseline characteristics were extracted: registration number, study design, sample size, age, sex, treatment, control, study duration and baseline SUA levels (Table 1).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…After further screening, 19 RCTs with 39 arms fulfilled the inclusion criteria and were eventually included in the present study (Figure 1). These RCTs incorporated 4218 adult participants with T2DM, and six SGLT-2 inhibitors were included: empagliflozin, [25][26][27][28] dapagliflozin, [29][30][31][32][33] canagliflozin, 34 ipragliflozin, [35][36][37][38] luseogliflozin [39][40][41] and tofogliflozin. 42,43 In addition, the following baseline characteristics were extracted: registration number, study design, sample size, age, sex, treatment, control, study duration and baseline SUA levels (Table 1).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…A previous study of ipragliflozin in a randomized trial setting also reinforced the SUA-lowering effect in parallel with beneficial renal effects. 11 From a clinical point of view, it is important to identify specific patient populations most likely to achieve the benefit of SGLT2 inhibition in terms of reducing SUA levels. 12 Notably, subgroup analysis in this study indicated mildly impaired renal function and elevated SUA levels at baseline as factors associated with the greater uric acid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…Однако корреляция не означает причинно-следственную взаимосвязь; вот почему нельзя утверждать, что увеличение рСКФ на фоне лечения ипраглифлозином способствует снижению уровня мочевой кислоты сыворотки крови у пациентов с нарушением функции почек и ожирением. Тем не менее полученные результаты согласуются с данными предшествующего исследования ипраглифлозина, показавшего, что улучшение функции почек сопровождалось снижением уровня мочевой кислоты сыворотки крови [38].…”
Section: Discussionunclassified